Albania : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses the Financial System Stability Assessment report on Albania. The IMF report states that the Albanian economy is weak, macroeconomic imbalances are large, and the financial sector faces several risks. Capital-to-asset ratios are sizable, but banks hold large amounts of government bonds that expose banks to sizeable losses in case of a sovereign debt re-pricing and balance sheets have deteriorated as a result of a rapid increase of nonperforming loans (NPLs). The authorities have taken steps to reduce the existing stock of NPLs with technical assistance from the World Bank.